Bone health and evaluation of bone mineral density in patients with premature ovarian insufficiency - Szeliga, Anna; Maciejewska-Jeske, Marzena; Męczekalski, Błażej (Menopause Review/Przegląd Menopauzalny, 2018)
Oestrogens exert an influence on skeletal homeostasis during growth and adulthood. Regulation of osteoclasts and osteoblasts generation and apoptosis and prolongation of the lifespan of osteocytes are some of their actions on bone metabolism. Premature ovarian insufficiency (POI) and associated loss of oestrogen action on osteoclasts leads to trabecular perforation and loss of connectivity. Lack of oestrogens acting on osteoblast progenitors also causes a decrease in critical bone mass. Postmenopausal hypoestrogenism is associated with an increase in the number of lymphocyte B-cells expressing nuclear factor B ligand (RANKL) in the bone marrow and elevated expression of RANKL by B-cells. Increased concentration of RANKL stimulates activation of osteoclasts and leads to oestrogen deficiency-associated bone loss. It has been proven that women with POI have decreased bone mineral density (BMD) measured in lumbar spine and femoral neck. The loss of bone mass associated with oestrogen deficiency is greater in trabecular than in cortical bone, thus women with POI have a significant decrease in BMD, particularly in the lumbar spine vertebrae. Smoking cessation, weight-bearing, and muscle-strengthening exercises on most days of the week, avoidance of excessive alcohol intake, and adequate supplementation of calcium and vitamin D are the main lifestyle rules necessary to avoid decline in BMD. The most important component of decreased BMD treatment in POI patients is systemic hormonal replacement therapy (HRT). HRT should provide hormonal balance and should mimic normal ovarian function as much as possible.